Recent Advances in Gastroenterology-14 - Tsai, H. H. Her Hsin (Jaypee Brothers Medical Publishers, 2021)
The aim of this book is to focus on the recent advances in gastroenterology-14. Clinical and basic research in the specialty of gastroenterology continues to advance at an unrelenting pace. This book consists of 14 chapters, which include surgical management of ulcerative colitis, microscopic colitis, eosinophilic gastroenteritis, gut mucus and its functional significance in health and disease, ten common errors in the treatment of helicobacter pylori infection, improving polyp detection at colonoscopy, post-endoscopic retrograde cholangiopancreatography pancreatitis, management of hepatitis c, and neurological complications in liver diseases. Gastroenterology is a wide, diverse specialty and Recent Advances in Gastroenterology aims to be a digest where the busy clinician and the budding trainee can delve into and acquire the expanding knowledge base in a single tidy volume.